Screening for mutations by enzyme mismatch cleavage with T4 endonuclease VII. - Youil, R (1995)
Each of four possible sets of mismatches (G.A/C.T, C.C/G.G, A.A/T.T, and C.A/G.T) containing the 8 possible single-base-pair mismatches derived from isolated mutations were examined to test the ability of T4 endonuclease VII to consistently detect mismatches in heteroduplexes. At least two examples of each set of mismatches were studied for cleavage in the complementary pairs of heteroduplexes formed between normal and mutant DNA. Four deletion mutations were also included in this study. The various PCR-derived products used in the formation of heteroduplexes ranged from 133 to 1502 bp. At least one example of each set showed cleavage of at least one strand containing a mismatch. Cleavage of at least one strand of the pairs of heteroduplexes occurred in 17 of the 18 known single-base-pair mutations tested, with an A.A/T.T set not being cleaved in any mismatched strand. We propose that this method may be effective in detecting and positioning almost all mutational changes when DNA is screened for mutations.